2021
DOI: 10.1007/s40953-021-00233-3
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Institutional Investors: Fair-Weather Friends or Smart Traders?

Abstract: We examine a theoretically robust but previously undocumented issue of what drives foreign portfolio investments into emerging markets. Foreign institutional investors (FIIs) are often blamed as fair-weather friends who pull out their investment at the first sign of trouble. Using a bottom-up approach, we explore this possibility. We demonstrate the influence of the firm-specific factors such as size, book to market ratio, the riskiness of the stocks, stock prices, dividend yield, liquidity, leverage, and earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…The northbound investments independently focus on fundamental information and reflect firms' quality. Our findings indicate that foreign capital investments help discover the value in the Chinese stock market and show smart and improvement effects (Kacperczyk et al, 2018;Venkatesh et al, 2021). Our results are also consistent with former studies on the advantages of market liberalization that found that sophisticated foreign investment helps alleviate the impact of noisy trading (Holmes & Wong, 2001), and investors from Hong Kong market contribute substantially to the price discovery process and that the A-share price incorporates more information after Connect (Sohn & Jiang, 2016).…”
Section: Comparison Between Northbound Investors and Domestic Retail ...supporting
confidence: 91%
“…The northbound investments independently focus on fundamental information and reflect firms' quality. Our findings indicate that foreign capital investments help discover the value in the Chinese stock market and show smart and improvement effects (Kacperczyk et al, 2018;Venkatesh et al, 2021). Our results are also consistent with former studies on the advantages of market liberalization that found that sophisticated foreign investment helps alleviate the impact of noisy trading (Holmes & Wong, 2001), and investors from Hong Kong market contribute substantially to the price discovery process and that the A-share price incorporates more information after Connect (Sohn & Jiang, 2016).…”
Section: Comparison Between Northbound Investors and Domestic Retail ...supporting
confidence: 91%
“…Despite global recessionary conditions, both purchases and sales of FIIs have steadily increased (Bollen and Whaley 2004). It was also found that even though the flows are highly correlated with the equity returns, they are more likely an influence rather than a cause of the returns (Venkatesh et al 2021). The key findings of Bachmann and Bolliger (2001) were changes in stock return volatility that were directly related to net buying pressure from public order flow, and that simulated delta-neutral option-writing trading strategies generate abnormal returns that match the deviations of the implied volatility above realized historical return volatilities (Wu et al 2022).…”
Section: Review Of the Literaturementioning
confidence: 96%
“…Therefore, the trading behavior of FIIs has a significant role in the movement of asset price in the Indian capital market (Fan and Feng 2022), especially in the derivatives segment where traders rely heavily on expected volatility rather than on asset fundamentals (Vardhan and Sinha 2016). Some of the existing literature has established a significant relationship between institutional investors' behavior and the expected volatility of the security market from developed economies (Venkatesh et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al (2020) found significant influence of political risk, market openness in terms of trade, stock market capitalisation, economy strength, and rate of return on investment in deciding investments from FPIs to the Indian stock market. Venkatesh et al (2021) studied the firm specific factors determining the influence on ownership of FIIs. The results revealed that firm specific factors such as earning per share, dividend yield, closing price, market risk, book to market ratio, return on assets, liquidity, and leverage have considerable influence on ownership decisions of FPIs.…”
Section: Background Of the Studymentioning
confidence: 99%